Edukasi DAGUSIBU (Dapatkan, Gunakan, Simpan, Buang) Obat pada Ibu Rumah Tangga di Desa Pematang Johar - Prabawa, Dimas Budi; Putri, Nurulita Alya; Rahmatia, Zilfa; Dama, Misda Milala; Wardani, Friska Ayu; Sambo, Desi Ratna; Syafitri, Natasya Fadhilah; Anisah, Siti; Arfianda, Donni; Putri, Vidia Windandari (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In society in general there is still a lot of inappropriate use of drugs. Providing educational information will increase public knowledge and increase their understanding. In this case, Al-Wasliyah Muslim Nusantara University students provided education about DAGUSIBU (Get, Use, Store and Dispose of) medicines correctly to housewives in Pematang Johar Village. Counseling is carried out on how to manage medicines properly so that it can increase public knowledge, especially housewives. This outreach activity for housewives begins with identifying the problems experienced by the community, which is done by approaching the community in Pematang Johar village and conducting interviews to gain information about their knowledge regarding the correct use of medicines using Powerpoint and projector media. The material presented in the counseling includes the 4 Right and 1 W aspects, namely Right Indication, Right Dosage, Right Patient Condition, Right Use and Beware of Side Effects of Drugs. This will increase housewives' knowledge of good and correct DAGUSIBU medicine.